A Study of Fourth-Order Hankel Determinants for Starlike Functions Connected with the Sine Function - Hai-Yan Zhang; Huo Tang (Journal of Function Spaces)
In this paper, upper bounds for the fourth-order Hankel determinant H41 for the function class Ss∗ associated with the sine function are given.